The Contribution of Oil Signs to the Petroleum Prospect in the Erindi Region, Albania - Enkela NOÇKA; Altin KARRIQI; Irakli PRIFTI (Smart Cities and Regional Development Journal)
Many wells have been drilled in Albania to search oil traps in the carbonate reservoirs of the Ionian area. One of them is the Nokova-1 well, drilled in the overflow front of the Berati anticline belt. Geographically it is in Erindi region, southern Albania.